Faktor Faktor yang Berhubungan dengan Insomnia pada Lansia yang di Rawat di RS Efarina Etaham Pematang Siantar - Sri Wahyuni Tarigan; Dasri Cahyana Lumbantungkup (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
The initial survey found 248 elderly people aged over 60-74 years in the last 3 months, elderly said they had difficulty sleeping, elderly said they slept less than 4 hours 30 minutes a day and night, easily woke up at night so that the time needed to fall back asleep after waking up at night was very short. The purpose of the study was to determine the factors associated with insomnia in elderly people at Efarina Etaham Hospital. The type of research used was analytical with a cross-sectional design. The population of all elderly people who were in Efarina Etaham Pematangsiantar Hospital during the last 3 months of 2024 was 248, with a sample size of 71 respondents. The data were analyzed using univariate and bivariate analysis using the Chi-square test with a p value of ≤ 0.05. The results of the study showed (84.5%) with elderly people, (53.5%) male gender, (32.4%) with severe stress, (87.3%) with the category of frequent caffeine consumption, (46.5%) with mild insomnia. There is a significant relationship between age and insomnia, gender with insomnia, lifestyle with insomnia, anxiety with insomnia. Based on the above phenomenon, it can be concluded that stress, age, caffeine consumption are related to insomnia. It is recommended for the elderly to reduce stress by getting closer to Allah SWT, and changing their lifestyle by reducing caffeine consumption so that they avoid insomnia and get peace of life.